2013
DOI: 10.4084/mjhid.2013.021
|View full text |Cite
|
Sign up to set email alerts
|

Lung Clear “Sugar” Cell Tumor and Jak V617f Positive Essential Thrombocythemia: A simple Coıncıdence?

Abstract: The primary clear cell tumor of the lung is an extremely rare benign tumor. This tumor is called “sugar tumor” since clear cell tumor of the lung contains abundant glycogen. We here present a case of lung clear cell tumor of the lung associated to essential thrombocythemia. To the best of our knowledge, there is no report about this association.A 44-Year-Old Woman admitted to our clinic with a 2-month history of fatigue. On physical examination, the spleen was 3 cm palpable below the left costal margin on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Between the two genders, there is a slight female preponderance among the CCTL patients. [10,11] Although the age range of the patients have been reported from 8 to 63 years old with the median age of 57 years; the neoplasm seems to present with a higher incidence in the elderly. [12] Usually, the presentation is an asymptomatic patient with an isolated coin lesion, so the lesion often is discovered inadvertently by via radiologic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between the two genders, there is a slight female preponderance among the CCTL patients. [10,11] Although the age range of the patients have been reported from 8 to 63 years old with the median age of 57 years; the neoplasm seems to present with a higher incidence in the elderly. [12] Usually, the presentation is an asymptomatic patient with an isolated coin lesion, so the lesion often is discovered inadvertently by via radiologic.…”
Section: Discussionmentioning
confidence: 99%
“…Over a longterm observation and research, some unique presentations have been reported in literatures, such as the finding about concurrently with minute pulmonary meningothelial-like nodules in the patient with rectal adenocarcinoma, [13] or concurrently with thrombocytosis (platelet count > 1,000,000/mm³), which was solved after removing the CCTL. [11,14] Radiographically, CCTLs generally present as solitary, round, peripheral and parenchymal nodules with smooth boundary, but without evidence of cavitation or calcification. The location of the tumor has no lobar preference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCTL has already been associated with other diseases, such as tuberous sclerosis complex ( 79 ), Birt-Hogg-Dube Syndrome, and essential thrombocythemia ( 26 , 27 ). However, in the malignant cases, it was not possible to determine the presence of risk factors strongly related to CCTL ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%